Metabolic Alterations in Different Stages of Hypertension in an Apparently Healthy Nigerian Population - M. A. Charles-Davies; A. A. Fasanmade; J. A. Olaniyi; O. E. Oyewole; M. O. Owolabi; J. R. Adebusuyi; O. Hassan; M. T. Ajobo; M. O. Ebesunun; K. Adigun; K. S. Akinlade; U. A. Fabian; et al. (International Journal of Hypertension)
Metabolic syndrome (MS) amplifies hypertension (HTN) associated with increased risk of cardiovascular disease (CVD). MS components and other CVD risk measures were investigated in different stages of hypertension. 534 apparently healthy Nigerian traders aged 18–105 years were participants of a cohort study. The International Diabetes Federation (2005) and the National High Blood Pressure Education Program Coordinating Committee criteria were used for MS and HTN classifications, respectively. Anthropometric indices were obtained by standard methods. Levels of fasting plasma glucose (FPG), total cholesterol (TC), triglyceride (TG), and high-density lipoprotein cholesterol (HDLC) were determined by enzymatic methods, while low-density lipoprotein cholesterol (LDLC) was calculated. Data analysed statistically were significant at P<0.05. 143 (26.8%), 197 (36.9%), and 194 (36.3%) of the traders had normotension, pre-HTN and HTN (stages 1 and 2), respectively. All indices tested except HDLC were significantly different among BP groups (P<0.05). Waist to hip (WHR) and waist to height (WHT) ratios were significantly different between HTN groups (P<0.05). HTN was associated with MS and female gender (P<0.05). Metabolic alterations and significant HTN were observed. Treatment of the individual components of the syndrome and improvement of modifiable metabolic factors may be necessary to reduce MS and high BP.